Scaling Up Rural Sanitation and Hygiene in Indonesia - World Bank (World Bank, Washington, DC, 2016)
This report is a synthesis of the technical assistance (TA) Scaling Up Rural Sanitation and Hygiene in Indonesia, carried out by the World Bank - Water and Sanitation Program (WSP). It was developed in consultation with the Directorate of Environmental Health, Directorate General of Public Health and Centre for Health Promotion of the Ministry of Health (MoH) and with key institutions in the focus provinces in West Java, Central Java, East Java, Bali, and West Nusa Tenggara. Reform in the rural sanitation sub-sector began in 2005 following the successful introduction of Community-Led Total Sanitation (CLTS) in 6 districts. In 2007, the Water and Sanitation Program (WSP) supported the Ministry of Health (MoH) to complement the use of CLTS with behavior change communication (BCC) and development of the sanitation market. This new approach was piloted at scale in 28 out of 29 districts in East Java Province in 2007-2011 under the Total Sanitation and Sanitation Marketing (TSSM) TA. Impressive results were achieved in just ten months, with 262 villages becoming Open Defecation Free (ODF). In response, MoH adopted the district-wide approach in 2008 and launched a new rural sanitation development strategy called Community-Based Total Sanitation (Sanitasi Total Berbasis Masyarakat) or STBM. The STBM strategy has three elements: demand creation through CLTS and BCC; supply chain improvement through developing the local sanitation market; and creation of and enabling environment through advocacy for local formal and informal regulations and resource mobilization. This project was was also complementary to a large-scale World Bank-funded program called PAMSIMAS, which has evolved from a project to a national platform through which the government intends to reach its newly adopted target of universal access to water supply and sanitation by 2019. Some of the key results and achievements are as follows : i) Well-functioning STBM Secretariat set up to co-ordinate STBM implementation nationwide, ii) Local government capacity in implementing STBM through demand creation, supply improvement and enabling environment increased, and iii) More effective STBM implementation at provincial and district Level. Some of the lesson learned: i) A capacity building framework to strengthen institutions at all levels is key for scaling up in a decentralized environment; ii) Well-crafted advocacy and communications are valuable for disseminating tested approaches and facilitating their adoption at scale; iii) Engagement of a range of institutions also strengthens campaign outreach; iv) An effective monitoring system is invaluable and it use should be formally integrated into the routine operations of government agencies; v) Local government can help to develop the rural sanitation market; and vi) The scaling up tested approaches can be enhanced greatly through their incorporation into established programmes.